2024
DOI: 10.1097/mcp.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Disparities across the continuum of lung cancer care: a review of recent literature

Lauren Kearney,
Tatyana Nguyen,
Katrina Steiling

Abstract: Purpose of review Lung cancer remains the leading cause of cancer mortality worldwide. Health disparities have long been noted in lung cancer incidence and survival and persist across the continuum of care. Understanding the gaps in care that arise from disparities in lung cancer risk, screening, treatment, and survivorship are essential to guiding efforts to achieve equitable care. Recent findings Recent literature continues to show that Black people, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Additionally, efforts should ensure that inequities do not arise because of barriers elsewhere in the screening continuum (eg, follow-up, cessation and oncologic treatment, and screening and treatment quality), which may further exacerbate noted racial and ethnic inequities in LC mortality burden. 28,32,34 Among screening-eligible persons nationally, we found that that UTD-LCS prevalence was higher among older persons than among younger persons, a finding consistent with other studies. 10,17 As evidence emerges of shifting late-stage diagnosis burden to younger ages, 35 this finding suggests the need for targeted demand (eg, education campaigns) and delivery (eg, addressing lower health care coverage, leveraging allied health professionals) interventions among younger LCSeligible persons.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, efforts should ensure that inequities do not arise because of barriers elsewhere in the screening continuum (eg, follow-up, cessation and oncologic treatment, and screening and treatment quality), which may further exacerbate noted racial and ethnic inequities in LC mortality burden. 28,32,34 Among screening-eligible persons nationally, we found that that UTD-LCS prevalence was higher among older persons than among younger persons, a finding consistent with other studies. 10,17 As evidence emerges of shifting late-stage diagnosis burden to younger ages, 35 this finding suggests the need for targeted demand (eg, education campaigns) and delivery (eg, addressing lower health care coverage, leveraging allied health professionals) interventions among younger LCSeligible persons.…”
Section: Discussionsupporting
confidence: 91%